2007
DOI: 10.1007/s10029-007-0299-z
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic parastomal hernia repair

Abstract: The laparoscopic approach to parastomal hernias is a new technique that offers many potential advantages over conventional open repairs. Based on our initial experience, this repair seems to be associated with a low recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 21 publications
1
21
0
6
Order By: Relevance
“…Controversy remains on whether to use mesh with a slit and keyhole or a mesh without a slit. After the first case reports of the modified Sugarbaker technique [5,7], acceptable low recurrence rates have been reported, but the length of follow-up was relatively short or was not stated [10,[13][14][15]. In another study that used the Sugarbaker technique with PTFE mesh, there were 8 recurrences in 41 patients [12].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Controversy remains on whether to use mesh with a slit and keyhole or a mesh without a slit. After the first case reports of the modified Sugarbaker technique [5,7], acceptable low recurrence rates have been reported, but the length of follow-up was relatively short or was not stated [10,[13][14][15]. In another study that used the Sugarbaker technique with PTFE mesh, there were 8 recurrences in 41 patients [12].…”
Section: Discussionmentioning
confidence: 88%
“…The first reports on use of mesh with a slit were also promising [6,8,9,11,15], but recently published results have been less satisfactory with higher failure rates [14,19,20]. In a retrospective study, Muysoms et al [14] reported 8 recurrences in 11 patients repaired with the keyhole technique, but only 2 recurrences in the subsequent 13 patients after changing to the Sugarbaker technique.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…B. Schweine hautkollagen oder humane azelluläre der male Matrix; außer Einzelbeschreibun gen existieren aber noch keine größeren in randomisierten Studien gewonnenen Erfahrungen [27,28]. Die Rezidivrate bei Verwendung der ZweiKomponentenNetze ist nach der Literatur und nach unseren Erfahrungen gering zwischen 0 und 7% [15,17,29,30]. In Einzelserien vor allem bei laparoskopi scher Anwendung werden jedoch auch hohe Rezidivraten zwischen 46 und 56% angegeben [31,32].…”
Section: Introductionunclassified
“…Die Angaben bzgl. Komplikationen wie Wundinfekte, Sepsis, Pneumonie oder Ileus schwanken erheb lich und liegen zwischen 3 und 33%, Ad häsionen, Arrosionen oder Fisteln wur den nicht beschrieben [29,30,31,32].…”
Section: Introductionunclassified